2021
DOI: 10.1038/s41598-021-98586-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of the hexanic extract of Serenoa repens compared to tamsulosin in moderate-severe LUTS-BPH patients

Abstract: In a subset analysis of data from a 6-month, multicenter, non-interventional study, we compared change in symptoms and quality of life (QoL), and treatment tolerability, in men with moderate to severe lower urinary tract symptoms associated with benign prostatic hyperplasia (LUTS/BPH) receiving tamsulosin (TAM, 0.4 mg/day) or the hexanic extract of Serenoa repens (HESr, 320 mg/day) as monotherapy. Symptoms and QoL were assessed using the IPSS and BII questionnaires, respectively. Patients in the treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…The improvement of 1.8 points on the BII in the HESr group is similar to that observed for other drugs used to treat LUTS/BPH, such as dutasteride and tamsulosin, which showed improvements of 1.7 points and 1.5 points, respectively, after 2 years of treatment in the COMBAT trial [27]. Improvements on the BII were reported in other publications evaluating the efficacy of the HESr; Alcaraz et al [11] reported a mean reduction of 2.2 points for patients receiving the HESr in a comparison with tamsulosin and a mean improvement of 2.7 points in an analysis comparing the HESr with tamsulosin and with a combination of both drugs [10].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The improvement of 1.8 points on the BII in the HESr group is similar to that observed for other drugs used to treat LUTS/BPH, such as dutasteride and tamsulosin, which showed improvements of 1.7 points and 1.5 points, respectively, after 2 years of treatment in the COMBAT trial [27]. Improvements on the BII were reported in other publications evaluating the efficacy of the HESr; Alcaraz et al [11] reported a mean reduction of 2.2 points for patients receiving the HESr in a comparison with tamsulosin and a mean improvement of 2.7 points in an analysis comparing the HESr with tamsulosin and with a combination of both drugs [10].…”
Section: Discussionsupporting
confidence: 82%
“…As has been shown in several previous studies [7,10,11,16], the improvements in symptoms and QoL associated with the HESr do not come at the expense of any relevant incidence of adverse effects. In the present sub-analysis, only 1% of patients receiving HESr reported an AE, and they were all classified as mild.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In terms of compliance, most (≈ 90%) patients in each medical treatment group took the medication with no difficulty [ 21 ]. In a subset analysis, the efficacy of HE S. repens was similar to that of tamsulosin in men with moderate to severe LUTS associated with BPH [ 23 ]. In patients who received monotherapy with HE S. repens 320 mg/day ( n = 384) or tamsulosin 0.4 mg/day ( n = 353), changes from baseline to 6 months in I-PSS total score, Q max , prostate volume and PSA were not significantly different between treatment groups.…”
Section: Therapeutic Efficacy Of He S Repensmentioning
confidence: 99%